160k views
5 votes
Please help me with this ! ! ! ! !

Please help me with this ! ! ! ! !-example-1

2 Answers

3 votes

The second equation tells you what 'n' is. It's "m-2" .

So you can simply write "m-2" in place of 'n' in the first equation.

Then the first equation says [ m - 2(m-2) = 8 ], and you should have no trouble solving that.

User Efremidze
by
5.0k points
3 votes

Answer:

First choice: m = -4

Explanation:

The second equation is already solved for n, so lets's use the substitution method and substitute m - 2 for n in the first equation.

m - 2n = 8

m - 2(m - 2) = 8

m - 2m + 4 = 8

-m + 4 = 8

-m = 4

m = -4

User Dima Patserkovskyi
by
4.6k points